Streptococcus pneumoniae Strains Isolated From a Single Pediatric Patient Display Distinct Phenotypes - Agnew, Hannah N.; Brazel, Erin B.; Tikhomirova, Alexandra; van der Linden, Mark; McLean, Kimberley T.; Paton, James C.; Trappetti, Claudia (Frontiers in Cellular and Infection Microbiology, 2022)
Streptococcus pneumoniae is the leading cause of bacterial paediatric meningitis after the neonatal period worldwide, but the bacterial factors and pathophysiology that drive pneumococcal meningitis are not fully understood. In this work, we have identified differences in raffinose utilization by S. pneumoniae isolates of identical serotype and sequence type from the blood and cerebrospinal fluid (CSF) of a single pediatric patient with meningitis. The blood isolate displayed defective raffinose metabolism, reduced transcription of the raffinose utilization pathway genes, and an inability to grow in vitro when raffinose was the sole carbon source. The fitness of these strains was then assessed using a murine intranasal infection model. Compared with the CSF isolate, mice infected with the blood isolate displayed higher bacterial numbers in the nose, but this strain was unable to invade the ears of infected mice. A premature stop codon was identified in the aga gene in the raffinose locus, suggesting that this protein likely displays impaired alpha-galactosidase activity. These closely related strains were assessed by Illumina sequencing, which did not identify any single nucleotide polymorphisms (SNPs) between the two strains. However, these wider genomic analyses identified the presence of an alternative alpha-galactosidase gene that appeared to display altered sequence coverage between the strains, which may account for the observed differences in raffinose metabolic capacity. Together, these studies support previous findings that raffinose utilization capacity contributes to disease progression, and provide insight into a possible alternative means by which perturbation of this pathway may influence the behavior of pneumococci in the host environment, particularly in meningitis.